Contributo Allo Studio della Vegetazione Dei Calcari Dolomitico-Giurassici della Sardegna: Vegetazione Del “Texile” di Aritzo E- “Toneri” di Belvì (Sardegna Centrale) - Martinoli, Giuseppe (Giornale botanico italiano, 1956)
Summary The vegetation of dolomitic and jurassic calcareous rocks has been studied and, particularly, the flora of Aritzo's and Belvi's ?Toneri? both located in the middle east of Sardinia. The flora of Aritzo's Toneri is very scanty because the calcareous tower-like blocks lie on a schistic ground and are very narrow. The predominant species are those with a short annual cycle: the only exception being the Quercus Ilex, growing on the walls of the calcareous rocks. The flora of Belvi's ?Toneri?, on the contrary, is more copious because this is larger than Aritzo's Toneri and here the erosions are less evident. As a matter of fact, here, besides the Quercus Ilex, there are some commun species of the ?macchia?. The flora of neighbouring schistic mountains is very different. The difference in the chemical characteristics of ground, as the Author claims, does not justify the great difference observed between the flora of calcareous and schistic ground. The last is typicaly mesophylic, Quercus Robur var. lanuginosa, Castanea sativa, Juglans regia, Ilex Aquifolium have been chiefly found. In the same region at a higher altitude xerothermic species, like Quercus Ilex, have been observed. The Author points out that the typical characteristic of Toneri's flora depends upon geological factors more than chemical or climatic one. In agreement with this point of view the Author found the same vegetation in Oliena, Tuttavista, Albo and Other dolomitic-jurassic calcareous Mountains of Sardinia.
doi: 10.1080/11263505609431614
Keywords: calcareous and schistic grounds; macchia species; Sardinia